2019
DOI: 10.1073/pnas.1807189116
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tools for thinking; arts, crafts, and design avocations; and scientific achievement among STEMM professionals

Abstract: Previous studies of science, technology, engineering, mathematics, and medical (STEMM) professionals have identified a common “mental toolkit” composed of 13 “tools for thinking” that STEMM professionals use in their problem raising and problem solving. The present research surveyed a convenience sample of 225 STEMM professionals to investigate whether these “thinking tools” are correlated with STEMM achievement measured variously as patents filed or licensed, companies founded, number of papers and books publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Robert Root-Bernstein et al (38) report on the role of arts, crafts, and design avocations in promoting creative thinking among 225 STEMM (STEM + Medicine) professionals. Tantalizing results, such as the correlation of metal-and woodworking avocations with patent production, suggest that increased training for STEMM students could be an effective way to improve their outcomes.…”
Section: Overview Of the Eventsmentioning
confidence: 99%
“…Robert Root-Bernstein et al (38) report on the role of arts, crafts, and design avocations in promoting creative thinking among 225 STEMM (STEM + Medicine) professionals. Tantalizing results, such as the correlation of metal-and woodworking avocations with patent production, suggest that increased training for STEMM students could be an effective way to improve their outcomes.…”
Section: Overview Of the Eventsmentioning
confidence: 99%
“…Teaching of such skills—commonly referred to as computational thinking (CT) skills—is nowadays widely recommended for educational institutions at all levels [87]. Many agree that CT and related design requires a combination of computational skills and skills in other fields of life, sciences and arts [78]. This combination is often referred to as integrated science, technology, engineering, arts and mathematics (STEAM) education [78].…”
Section: Introductionmentioning
confidence: 99%
“…Many agree that CT and related design requires a combination of computational skills and skills in other fields of life, sciences and arts [78]. This combination is often referred to as integrated science, technology, engineering, arts and mathematics (STEAM) education [78]. In addition, many stress the importance of soft skills, such as creativity, communication and critical thinking skills, often referred to as 21st century (C21) competencies [84].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that polymathy may be a crucial element for creativity, especially in contexts that are novel, transdisciplinary, or which require a shift in perspective (Sriraman and Søndergaard, 2009;Gombrich, 2016;Root-Bernstein and Root-Bernstein, 2020b). However, despite the general claim that creativity and innovation are important and despite the role of polymathy for creativity and innovation to flourish (Simonton and Cassandro, 2010;Root-Bernstein et al, 2019), the dominant culture in both the industry and academia is that of specialization. To be successful as a professional, one is expected to focus very narrowly, avoid giving "mixed messages" regarding one's expertise, and often advised to split one's interests and passions between those that are "vocational"-and deserve one's true attention-and those that are "avocational, " and should not take precious time away from one's main specialty (see also Root-Bernstein and Root-Bernstein, 2004;Root-Bernstein, 2009;Araki, 2018).…”
Section: Introductionmentioning
confidence: 99%